Implementasi Pengembangan Madrasah dan Sekolah Islam Unggulan Sebagai Upaya Peningkatan Kualitas Pendidikan Islam - Nanang Budianto (FALASIFA : Jurnal Studi Keislaman, 2017)
Today many educational institutions in Indonesia which is developing a superior education system, including institutions of Islamic education. Islamic schools or madrasah are the flagship of Islamic educational institutions that create superior organizational culture and climate and effective. This paper has produced a review and new view on the development of madrasah and Islamic schools of excellence. To develop the pre-eminent Islamic schools or madrasah, are needed: (1) carrying capacity of an effective and functional, such as a superior human resources, facilities and infrastructure (classrooms representative, libraries and laboratories), support facilities (boarding, mosque). (2) Careful planning and mature designed in accordance with the vision, mission and objectives of the institutional school, requires analyzing the needs of academic and institutional systems, and understand the geographical and cultural context. (3) Building a shared commitment, and build mind set collectively, always give priority to continuous innovation, and utilizing information technology as an effective learning resource.Â Keywords: Islamic schools flagship, carrying the school, SDM